THE IMPORTANCE OF ATTENTION AND CONCENTRATION IN SPORTS SCOPE (Fiep Bulletin - online, 2016)
This paper's objective is to conduct a reflection about the importance of sports psychology, thus presenting significant aspects that contribute to a better performance in sports, which is a literature review based on renowned authors who claim that psychologists and coaches who deal with the practical part, the physical development of their athletes, should learn and understand the theoretical and methodological field, so each party must learn from the other. Among these, various magazines and articles are enumerated available from Scielo, Master Editora, Revista Mineira de EFI, Biblioteca virtual Univap, among others. The aim of this study is to alert coaches and sports psychologists, it is essential to work together, as they have several concepts and understandings of what is practical and what is science, so sharing with the athlete basic knowledge and techniques for a better mental development, where it is involved many individuals with diverse backgrounds with a common interest: to know more about the athlete and the sport, aiming to help understanding, explaining and predicting events. Under this basis we can develop good cooperation that will help both the Sport Psychology as well as sports, teaching principles and psychological foundations of learning processes and teaching, developing psychological intervention measures for education, training and competition, or acting with psychological interventions in sports through counseling and monitoring measures. From the theme it is possible to understand how psychological factors influence physical performance and it is understood how the participation in these activities affects the emotional development, health and well being of individuals in these environments. Therefore, it is possible to conclude from the studies mentioned that for an athlete to be considered "complete" it is necessary that besides physical training, the psychological aspects are also worked. A training mind control with concentration exercises, where the athlete has the ability to shift the attention quickly to important factors and disregard irrelevant ones.
Keywords: concentration; psychology; sport.